Wang procedure for treatment of asphyxiating thoracic deformity - Wenlin Wang; Weiguang Long; Yang Liu; Bin Cai (Elsevier, 2022)
Asphyxiating thoracic dystrophy is a rare and dangerous thoracic deformity, and its operation is challenging. In the past, several operations have been reported, but they all have disadvantages. Wang procedure is a new method for the treatment of pectus excavatum. Because this procedure can effectively eliminate various chest wall depressions, we use it in the treatment of asphyxiating thoracic dystrophy. This paper reports the use of Wang procedure in a 10-year-old child with asphyxiating thoracic dystrophy, and the result of the operation was satisfactory.